Sodium Hyaluronate in the Treatment of Dry Eye Syndrome: A Systematic Review and Meta-Analysis - Bryan Chin Hou Ang (Nature Portfolio, 2017)
Abstract This systematic review and meta-analysis compares sodium hyaluronate (HY) with non-HY based artificial tears in the treatment of dry eye syndrome. A literature search for clinical trials comparing HY against non-HY preparations was conducted across PubMed, Cochrane Central Register of Controlled Trials and Scopus databases from inception up to May 2016. Majority of the 18 studies selected for review showed superiority of HY in improving ocular staining and symptoms. Randomized controlled trials (RCTs) examining Schirmer’s I (SH) and tear breakup time (TBUT) underwent further meta-analyses with calculation of pooled standardized mean differences (SMDs) with 95% confidence intervals (CIs). 7 RCTs including 383 eyes randomized to HY and 596 eyes to non-HY preparations underwent meta-analysis for SH. 9 RCTs including 458 eyes randomized to HY and 651 eyes to non-HY preparations underwent meta-analysis for TBUT. By fixed-effects modelling, HY demonstrated greater improvement of SH compared to non-HY preparations (SMD, 0.238; 95% CI, 0.107 to 0.369; p < 0.001). By random-effects modelling, HY demonstrated less improvement of TBUT (SMD, −0.566; 95% CI, −1.099 to −0.0336; p = 0.037). In summary, neither preparation was shown to be consistently superior across all outcome measures. The difference in effect between preparations on SH and TBUT was not clinically significant.